Separately continuous mappings with values in nonlocally convex spaces - Karlova, O. O.; Maslyuchenko, V. K. (Ukrains’kyi Matematychnyi Zhurnal, 2007)
We prove that the collection (X, Y, Z) is the Lebesgue triple if X is a metrizable space, Y is a perfectly normal space, and Z is a strongly σ-metrizable topological vector space with stratification (Z_m)^∞_m=1, where, for every m N, Z_m is a closed metrizable separable subspace of Z arcwise connected and locally arcwise connected.